Pembelajaran dan Pembinaan Karakter Santri: Refleksi Pengalaman Praktik Mengajar di Pondok Pesantren Fath Darut Tafsir Bogor - Ansory, Isnan; Jariah, Ainun (Pusat Penelitian dan Pengabdian Masyarakat STIQ ZAD Cianjur, 2025)
Character education and development for boarding school students within the boarding school environment is one of the key priorities in Field Experience Practice (FEP) as a tangible contribution to fostering a generation that loves the Qur’an and possesses noble character. This activity was conducted at Pondok Pesantren Fath Darut Tafsir Bogor using a descriptive qualitative approach through the method of reflective experience. The author had the opportunity to participate in the learning process of various subjects, halaqah development, and other boarding school activities. The results of this service show an increase in the understanding and application of Islamic character values by the students. This experience reinforces that character development based on Qur’anic values and direct practice at the boarding school has a significant impact on the formation of the students’ personalities.